IT/OT convergence and cyber security. Issue 12 (December 2021) - Maleh, Yassine
Abstract : A study by Forrester, commissioned by Fortinet, reveals the growing exposure of industry players to cyberthreats – one of the consequences of digital transformation. 1 The lack of collaboration between IT teams and those in charge of industrial or operational technology (OT) is also a hindrance to cyber security for companies wishing to take full advantage of IT/OT convergence to increase their competitiveness.